Resonant Configuration Topology Exploration for Inductive Link Power Transfer - S. Hafiz; Zarimin Zaharudin; Sheroz Khan; Nur Shahida Binti Midi; John Tan Teng Hwang; Kushsairy Abdul Kadir; Jawad Ali Shah (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper investigates the performance of circuit topology used in wireless power applications to optimize the level of maximum efficiency. We analyse the series and the parallel resonant topologies for use in an inductive coupling link to derive power transfer efficiency expressions verified using MATLAB. We look into the two topologies into the link under resonant conditions for selectively supplying the device with power. The results are obtained analytically which are verified subsequently by MATLAB simulation. We then analyse the links to see how maximum power transfer efficiency for a given pair of coils can be achieved. The topology at a given tuning frequency is used for powering a selected resistive load. The method is presented using a given pair of coils simulated and the results agree well with the theoretical explanation and derivations.